A Linear Regression Predictor for Identifying N6-Methyladenosine Sites Using Frequent Gapped K-mer Pattern - Y.Y. Zhuang; H.J. Liu; X. Song; Y. Ju; H. Peng (Elsevier, 2019)
N6-methyladenosine (m6A) is one of the most common and abundant modifications in RNA, which is related to many biological processes in humans. Abnormal RNA modifications are often associated with a series of diseases, including tumors, neurogenic diseases, and embryonic retardation. Therefore, identifying m6A sites is of paramount importance in the post-genomic age. Although many lab-based methods have been proposed to annotate m6A sites, they are time consuming and cost ineffective. In view of the drawbacks of the intrinsic methods in RNA sequence recognition, computational methods are suggested as a supplement to identify m6A sites. In this study, we develop a novel feature extraction algorithm based on the frequent gapped k-mer pattern (FGKP) and apply the linear regression to construct the prediction model. The new predictor is used to identify m6A sites in the Saccharomyces cerevisiae database. It has been shown by the 10-fold cross-validation that the performance is better than that of recent methods. Comparative results indicate that our model has great potential to become a useful and effective tool for genome analysis and gain more insights for locating m6A sites. Keywords: N6-methyladenosine, RNA modifications, novel feature extraction algorithm, frequent gapped k-mer pattern, linear regression, Saccharomyces cerevisiae database, 10-fold cross-validation, genome analysis